ANALISIS PENGARUH MOTIVASI KERJA APARATUR TERHADAP KUALITAS LAYANAN CIVIL : STUDI PADA KANTOR KELURAHAN LOK BAHU KECAMATAN SUNGAI KUNJANG KOTA SAMARINDA - Novita, Emiliya (PREDIKSI, 2012)
This study aimed to determine whether work motivation Apparatus having a positive influence on quality of the Civil Service Lok Shoulder Village Office, District Kunjang River, the city of Samarinda.            The results showed that there is a positive and significant effect of the variable on the variable Work Motivation Reform Civil Service Quality On Lok Shoulder Village Office, District Kunjang River, the city of Samarinda. It can be seen from the results of a statistical test in which the correlation coefficient (r) is equal to 0.712. The result was greater when compared to the table of critical prices Product Moment Correlation coefficients (Pearson) for n = 16 at the 5% significance level, ie 0.497. Or it can be said also that rhit = 0.712> rtab = 0.497, which means that there is a strong relationship between the two variables.